The circadian cryptochrome, CRY1, is a pro-tumorigenic factor that rhythmically modulates DNA repair - Shafi, Ayesha; McNair, Chris M.; McCann, Jennifer J.; Alshalalfa, Mohammed; Shostak, Anton; Severson, Tesa M.; Zhu, Yanyun; Bergman, Andre; Gordon, Nicolas; Mandigo, Amy C.; Chand, Saswati N.; Gallagher, Peter; et al. (Nature Communications, 2021)
Mechanisms regulating DNA repair processes remain incompletely defined. Here, the circadian factor CRY1, an evolutionally conserved transcriptional coregulator, is identified as a tumor specific regulator of DNA repair. Key findings demonstrate that CRY1 expression is androgen-responsive and associates with poor outcome in prostate cancer. Functional studies and first-in-field mapping of the CRY1 cistrome and transcriptome reveal that CRY1 regulates DNA repair and the G2/M transition. DNA damage stabilizes CRY1 in cancer (in vitro, in vivo, and human tumors ex vivo), which proves critical for efficient DNA repair. Further mechanistic investigation shows that stabilized CRY1 temporally regulates expression of genes required for homologous recombination. Collectively, these findings reveal that CRY1 is hormone-induced in tumors, is further stabilized by genomic insult, and promotes DNA repair and cell survival through temporal transcriptional regulation. These studies identify the circadian factor CRY1 as pro-tumorigenic and nominate CRY1 as a new therapeutic target.